Pengaruh Digital Marketing dan Kualitas Produk terhadap Keputusan Pembelian (Studi Kasus : UMKM Rokupang Cabang Karawang) - Sari, Sukarn Novita; Wirawan, Dika (Institut Ilmu Sosial dan Manajemen STIAMI, 2022)
Customer satisfaction currently plays an important role in increasing sales. One of them is utilizing digital marketing technology in the marketing process and increasing interest in purchasing a product. This study discusses the relationship between the influence of digital marketing and product quality on purchasing decisions for the karawang branch of rokupang. The sampling technique used in this study used Probability Sampling Technique. Multiple Regression Analysis is used in the process of analyzing data. The results of this study showed that digital marketing has a partial and significant effect on purchasing decisions by 65.8%, and product quality has a partial and significant effect on purchasing decisions by 80.5%. Digital marketing and product quality have a simultaneous and significant influence on purchasing decisions by 81.1%, and 18.9% is explained by other factors outside the model that are not examined